On the history of abortion from antiquity to the present day, with a focus on Central Europe and Germany - Dienerowitz, Florian; David, Matthias (Archives of gynecology and obstetrics, 2026)
The question of how to deal with a pregnancy, whether desired or unwanted, is a complex biological, ethical, social, and medical issue going back for millennia. Every form of regulatory approach to this issue is culturally and temporally specific and is therefore subject to continuous change. Our look at its history and the medical, legal, and religious background begins in ancient times, progresses through history, and ends with a focus on the second half of the nineteenth century and especially the twentieth century in Germany. These ethical, moral, and medical questions are likely to have been discussed in a similar way in other parts of the Western world.
Online veröffentlicht: 6. Januar 2026
Gesehen am 24.02.2026